2022
DOI: 10.1136/bmjsrh-2021-201399
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with female genital mutilation: a systematic review and synthesis of national, regional and community-based studies

Abstract: BackgroundThis systematic review aimed to identify and describe the factors that influence female genital mutilation/cutting (FGM/C).MethodsSearches were conducted in Medline, PsycInfo, Web of Science, Embase and the grey literature from 2009 to March 2020 with no language restrictions, using related MESH terms and keywords. Studies were included if they were quantitative and examined factors associated with FGM/C. Two researchers independently screened studies for inclusion, extracted data and assessed study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 69 publications
0
25
0
1
Order By: Relevance
“…This systematic review and meta-analysis were part of a larger project on FGM/C prevalence and its determinants [ 6 , 17 ]. Cohort or cross-sectional studies that reported on FGM/C prevalence at the national level, using representative samples or population-based methods, were included in the systematic review and meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review and meta-analysis were part of a larger project on FGM/C prevalence and its determinants [ 6 , 17 ]. Cohort or cross-sectional studies that reported on FGM/C prevalence at the national level, using representative samples or population-based methods, were included in the systematic review and meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Nationally representative data show that there is a decline in the prevalence of FMG/C, but this is not universal across countries [ 1 , 4 , 5 ]. FGM/C persists due to religious, social, and cultural factors [ 6 ]. It is commonly believed to create better marriage prospects because of beliefs related to morality, hygiene, and aesthetics; FGM/C is also believed to curb sexual urges and maintain virginity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion and exclusion criteria. This systematic review and meta-analysis were part of a larger project on FGM/C prevalence and its determinants [7,19]. Cohort or cross-sectional studies that reported on FGM/C prevalence at the national level, using representative samples or populationbased methods, were included in the systematic review and meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Nationally representative data show that there is a decline in the prevalence of FMG/C but this is not universal across countries [1, 5, 6]. FGM/C persists due to religious, social, and cultural factors [7]. It is commonly believed to create better marriage prospects because it associates with morality, hygiene, and aesthetics; FGM/C is also believed to curb sexual urges and maintain virginity [8].…”
Section: Introductionmentioning
confidence: 99%
“…An extreme manifestation of this sense of female anatomy inadequacy is female genital mutilation (FGM). This is a deeply rooted practice, performed for complex sociocultural factors in some cultures, and has affected over 200 million people (El-Dirani et al, 2022;WHO, 2022). It involves the partial or total removal of external female genitalia for non-medical reasons.…”
Section: The Importance Of Diverse and Accurate Descriptions Of Genit...mentioning
confidence: 99%